Effect of DC Pre-stress on Space Charge and Electrical Tree in XLPE with Needle-Plate Electrodes - Xiaobin XU; Aijing LIU; Yanjie LE; Hechen LIU; Zhanpeng GUO; Yunpeng LIU (Zhongguo dianli)
Space charge is one of the main factors that affect the electrical tree characteristics of HVDC cable insulation. Based on the bipolar charge transport model, this paper simulates the space charge distribution characteristics of the two-dimensional needle plate electrode model under ±20 kV、±22.5 kV and ±25 kV DC pre-stress with a duration of 3 600s, and makes a comparative analysis between the space charge distribution characteristics and the DC grounded electrical tree initiation characteristics. The results show that the space charge density and injection depth increase with the increase of the pre-stress and time, and the initiation length of DC grounded electrical tree increases with the increase of pre-stress duration and amplitude. There is a high similarity between space charge distribution characteristics and electrical tree initiation characteristics. The space charge distribution near the needle tip is the main reason for the difference in the initiation characteristics of the grounded electrical tree.